Shariah Accountability Practice Of Malaysian Foreign-owned Islamic Banks And Bahrain Islamic Banks - Rosnia Masruki; HarizHilmi Khairulannuar; Bablu Kumar Dhar (Science and Engineering Research Support Society, 2024)
Indexed by ERA